Investors’ Objectives and Foreign Direct Investment inflows in African Regions: Array - Aberu, Felix; George, Emmanuel Oladapo; Adegboyega, Soliu Bidemi (EuroEconomica, 2021)
This study increases the frontier of FDI inflows literature by investigating the impact of investors’ objectives on FDI inflow in the five (5) African regions between the periods 1996 to 2020. To achieve this aim, panel data techniques (system GMM, fixed effects and PMG) were employed on a sample of selected countries across the five (5) African regions. The empirical results showed that market seeking objective influenced FDI inflows activities in the selected countries across the five (5) African regions. Meanwhile, efficiency seeking objective also determined FDI inflows in the selected regions but with the elasticity of 0.09 that is less significant for specifications for the period of investigation with SGMM technique. Furthermore, the pooled mean group estimation technique confirmed the structural and behavioural differences in FDI inflows among the five (5) African regions when analyzed separately, FDI inflows in all African regions was market and efficiency seeking objectives determined. However, from the empirical findings, there are resultant policy implications. These policy implications include that, African regions should intensify efforts to engage in an integrated common market that is FDI inflow induced and ensuring evidence based policies that are liberalization friendly such as reduction of taxes, licenses and insecurity.